2021
DOI: 10.1186/s40170-021-00265-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory metabolic profile of South African patients with prostate cancer

Abstract: Background Men with African ancestry are more likely to develop aggressive prostate cancer (PCa) and to die from this disease. The study of PCa in the South African population represents an opportunity for biomedical research due to the high prevalence of aggressive PCa. While inflammation is known to play a significant role in PCa progression, its association with tumor stage in populations of African descent has not been explored in detail. Identification of new metabolic biomarkers of inflam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Several studies have revealed specific metabolic alterations in PCa patients by comparing prostate tumors of different grade. Furthermore, different systemic and local metabolic alterations have consistently been associated with PCa risk and progression [111][112][113][114][115][116]. In line with this, in a recent study by Gómez-Cebrián et al, the specific metabolomics profile of high-grade PCa patients was characterized on the basis of the alterations in metabolite levels identified in the serum and urine of PCa patients with different tumor grades [100].…”
Section: Pca Subtypingmentioning
confidence: 79%
“…Several studies have revealed specific metabolic alterations in PCa patients by comparing prostate tumors of different grade. Furthermore, different systemic and local metabolic alterations have consistently been associated with PCa risk and progression [111][112][113][114][115][116]. In line with this, in a recent study by Gómez-Cebrián et al, the specific metabolomics profile of high-grade PCa patients was characterized on the basis of the alterations in metabolite levels identified in the serum and urine of PCa patients with different tumor grades [100].…”
Section: Pca Subtypingmentioning
confidence: 79%
“…Using untargeted metabolomics techniques, Mayerle demonstrated that a biomarker signature (nine metabolites and an additional CA19-9) could be identified as differential diagnoses of PDAC and CP (Mayerle et al, 2018). In addition, inflammatory metabolites identified by serum metabolomics can also stratify tumor and improve diagnosis of patients with aggressive tumor (Cacciatore et al, 2021). The discovery of metabolomics for tumor blood biomarkers can be extended to various aspects, which include the discovery of significantly different metabolites, changes in the tumor metabolic and direct identification of tumors and inflammation.…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Thus, data from multiple research groups have demonstrated changes to circulating lipid levels in PCa patients. Lipid metabolites, sterols, steroids, and phospholipids in the serum or plasma might be good candidates for PCa detection, and findings correlating serum metabolomics to PCa may potentially be used for the development of new therapies for PCa [58].…”
Section: Serum Lipid Metabolites In Pca Patientsmentioning
confidence: 99%